Perancangan Sistem It Inventory Dengan Integrasi Ceisa Bea Cukai Berbasis ERP Pada PT. Topjaya Antariksa Electronics - Amelia Rahma Dewi; Samsoni (CV. Multi Kreasi Media, 2023)
Bonded Logistic Center is a business to make export and import transcation but the definition of Bonded Logistic Center is “A Bonded Piling Place for storing goods originating outside the customs area and/or goods originating from other places within the customs area, may be accompanied by 1 (one) or more simple activities within a certain period of time to be re-issued.” To make a transcation in Bonded Logistic Center the holding of business should have an IT Inventory System that can be checked in real time by the responsible Directorate General of Customs and Excise. According to Directorate General of Customs and Excise law No. PER-09/BC/2014 about